Penerapan Media Audio Visual Dalam Meningkatkan Hasil Belajar Siswa Pada Pembelajaran PAI Kelas IV SDN 09 Lanai Sinuangon - Syahri, Ika Puspita (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) through the use of audio-visual media among fourth-grade students at SDN 09 Lanai Sinuangon. The method used is classroom action research (CAR) based on Kurt Lewin's model, comprising four stages: planning, implementation, observation, and reflection. The study was conducted in two cycles. The results showed that using audiovisual media could improve students' learning outcomes. In the first cycle, the students' completion rate increased from 47% in the pre-cycle to 53%. After improvements were made in the second cycle, the completion rate rose to 66.67%. Although there was an improvement, the results indicate that some students still require additional guidance to meet the success criteria. This study underscores the importance of continuous evaluation and the application of relevant learning media to enhance the quality of education.